The cooperation between the African Union and the European Union in the field of migration and collective security as an absolute imperative - Diallo, Boubacar Sidi (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2020)
At a time when Africa is strengthening its attractiveness, acquiring its own story and arousing the interest of new partners, and when Europe is going through an important economic and institutional crisis, what can the new bases for cooperation between the European Union and the African Union be? The Abidjan summit in November 2017 offered an opportunity to reflect on the achievements of bi-regional cooperation between Africa and Europe in the field of migration, peace and security. It emphasized the priority of education, support for sustainable and inclusive development, and multi-sector cooperation, stating that all of them be carried out within the framework of horizontal cooperation favouring reciprocal Africa-European Union contributions. However, one must be aware of the constraints, weighing on both partners, which hinder implementation of the agreed strategies.